Fiscal policy and futures contracts: The case of natural persons in Mexico (Monte Carlo simulation and binomial valuation) - González Aréchiga-Ramírez Wiella, Bernardo; Díaz Tinoco, Jaime; Venegas Martínez, Francisco (Estudios Económicos de El Colegio de México, 2000)
This paper determines the tax rate, withheld by the clearing member, on gains from listed futures that guarantees the same tax revenue as that of the current tax treatment of noncorporate individual investors residents in Mexico. The proposed tax policy reduces costs and improves market liquidity and efficiency. The paper develops two models to estimate de break-even tax: 1) a Monte Carlo simulation model, and 2) a binominal model of asset pricing. This work pays special attention to the robustness of the results by modifying the probabilistic assumptions and the values of the parameters.